A utilização do Flashcards no ensino de língua estrangeira (espanhol) no Instituto Federal do Amapá - NUNEZ, Maria Estela Gayoso (2023)
The teaching methodology is a set of didactic procedures, characterized by their teaching methods and techniques, used with the purpose of achieving success in the teaching-learning process. This study aimed to provide EPT professionals of the technical course in mining with subsidies that improve and diversify their pedagogical praxis. Among other aspects, the research had the specific objective of verifying how the active methodology, flashcards, can help in teaching Spanish to students in the 3rd year of an integrated technical course in mining. As a pedagogical practice, a Glossary was provided, which was developed through an active methodology (Flashcard), based on gamification, enabling the optimization of student learning on the subject of some technical terms in mining. At first, the research verified whether foreign language teachers at the Federal Institute of Amapá - IFAP make use of active methodologies within the training process. From this, an active methodology, based on gamification, was proposed in order to be used in Spanish language classes for students of the integrated technical course in mining (3rd year). The research was characterized by its applied nature, containing a qualitative approach and through a bibliographic review. It is noteworthy that data collection took place through a semi-structured questionnaire for the construction of this dissertation. After the development of the research, the various benefits arising from the use of flashcards in pedagogical practices were understood, such as autonomy, encouragement of oral interaction in Spanish, since they provide memorization and understanding of contents in a more authentic and accessible way. . It is concluded that this methodology, flashcards, can develop different skills and abilities in different areas of knowledge.